HUBUNGAN ANTAR KUALITAS TIDUR DENGAN KONSENTRASI BELAJAR SISWA SMK PUSTEK SERPONG TANGERANG SELATAN TAHUN 2020 - Nerli Adria Sinabutar; Nur Indah Pratiwi (STIKes IMC Bintaro, 2022)
Sleep quality is a complex phenomenon which includes aspects of length ofsleep, frequency of wakeups and aspects of sleep time and sleep. Sleep quality is considered very important to a person's physical and mental condition. This is based on the sleep function, where sleep is believed to allow the body to repair itself, affect the balance of hormones in the body, restore and rest physically after daily activities, reduce stress and anxiety, repair damaged body cells, store energy, and improving immunity, increasing the ability to concentrate when doing daily activities. The purpose of this study was to determine the relationship between sleep quality and learning concentration of students in SMK Pustek Serpong Tangerang Selatan 2021. This research method used a quantitative research design with a cross sectional approach. The sample technique used by researchers is the random sampling technique with a total of 64 respondents. The results showed that the results of the chi square test showed a relationship between sleep quality and learning concentration with a p-value of 0.000 <0.05. Conclusions and suggestions are expected to be useful information for students and find out about the quality of sleep and learning concentration.